A Novel Route for Fabrication of Stable CsPbI3 Perovskite Thin Film by Thermal Evaporation. Issue 17 (6th May 2019) - Gupta, Yashika; Palakkandy, Arun; V.Syrotyuk, Stepan; Kumar, Kuldeep; Arora, Smriti
Abstract: Perovskite thin films hold promise as a potential candidate for high efficiency solar cells. In recent years, a wealth of results has been published on CsPbI3 thin films. However, most of the literature reports that CsPbI3 perovskite films are prone to aging where black colored CsPbI3 films with cubic lattice change to yellow colored films with orthorhombic lattice upon exposure to ambient conditions. This poor stability presents itself as a major challenge in utilization of CsPbI3 for device applications. This manuscript presents an alternate route for fabricating stable CsPbI3 thin films using thermal evaporation. Experimentally, our samples were found to be stable, visually and structurally, over a period of six months. Even annealing of the samples did not induce structural changes. Abstract : The work describes a simple and novel method to obtain CsPbI3 perovskite by thermal evaporation. The formation of cubic‐phase perovskites was experimentally confirmed by X‐Ray Diffraction and UV‐visible spectroscopy. Abinit calculations showed the variation of band gap with lattice constant. The samples have been tested over 7–8 months to confirm the stability.